Ανάλυση και σχεδιασμός δομικών συστημάτων μεταλλικών κατασκευών - Βορκά, Μαρία (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This diploma study aims the modeling, analysis and design of two different structural steel construction systems. Both structural systems are based on the same five-store building, which is submitted under the simultaneous effect of gravity loads and seismic action. For lateral stability, the first building includes moment resisting frames and the second Concentric Bracings Frames. The simulation, analysis and design of two structural systems made in STAAD.pro software. according to Eurocodes design 0, 1, 3 and 8. In the seismic analysis, the modal spectral analysis method is applied. Finally, there is the comparison of the results obtained from analysis of those two types of structural systems and conducted some conclusions.
Keywords: Structural steel construction systems; Lateral stability; Moment resisting frames; Concentric bracings frames; Modal spectral analysis; Δομικά συστήματα; Πλευρική ευστάθεια; Πλαίσια παραλαβής ροπής; Πλαίσια με κεντρικούς συνδέσμους δυσκαμψίας; Ιδιομορφική φασματική ανάλυση